Evaluasi Sanitasi Di Sekolah Dasar Negeri 07 Kubu Gulai Bancah, Kecamatan Mandiangin Koto Selayan, Kota Bukittinggi, Tahun 2023 - Erian Fatria (Program Studi Magister Manajemen Lingkungan, 2023)
Healthy schools generally have the main focus to create a school atmosphere with a healthy learning environment both physically and mentally. It is characterized by school conditions that are clean, neat, orderly, beautiful and uphold the values of environmental harmony in achieving the goals of a superior and outstanding school. School sanitation is very important because schools are places that have a strategic role, especially educating and preparing the next generation of the nation. The purpose of this study was to provide information related to the sanitation of State Elementary School 07 Kubu Gulai Bancah, Mandiangin Koto Selayan District, Bukittinggi City in 2023. This research method is a quantitative method with a descriptive approach with the aim of obtaining an overview of sanitary conditions. The subject of this research was State Elementary School 07 Kubu Gulai Bancah. The data used in this study are primary data or data obtained directly based on observations. The results showed that the sanitary conditions of State Elementary School 07 Kubu Gulai Bancah, Mandiangin Koto Selayan District, Bukittinggi City have not all met health requirements. Therefore, it is necessary to improve health facilities in schools to support existing sanitation efforts, so that they can spur school achievement towards adiwiyata and reduce adverse risks for all school residents.